BEHAVING IN INTERCULTURAL SETTINGS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Annotation:This article explores essential strategies for navigating intercultural settings with sensitivity and understanding. Drawing on principles of cultural awareness, empathy, effective communication, and respect for cultural norms, it provides practical guidance for individuals seeking to interact successfully in diverse cultural contexts.